Pre-operative intravenous feeding–a controlled trial. Issue 646 (August 1979) - Heatley, R. V.; Williams, R. H.; Lewis, M. H.
Abstract : Seventy-four patients with a pre-operative diagnosis of stomach or oesophageal cancer were entered into a randomized, controlled clinical trial to assess the value of a short course of pre-operative intravenous nutrition. The effectiveness of this treatment was assessed by the clinical course and monitored by means of immune and biochemical profiles. Pre-operative parenteral nutrition given over a 7-10-day period resulted in a significant reduction in the incidence of postoperative wound infections. Clinical benefit was confined to those patients who had a low serum albumin on admission to hospital. It is doubtful whether this limited benefit justifies the routine use of intravenous feeding, with its attendant hazards, in the pre-operative preparation of patients with upper gastrointestinal cancer.